THE ROLE OF VISUAL ELEMENTS IN DAILY JOURNALING AS AN EFFORT TO REDUCE ANXIETY AMONG COLLEGE STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Jihanni Sheila Utami; Agus Juhana (Universitas Negeri Semarang, 2025)
Mental disorders are conditions that can affect anyone, and college students are particularly vulnerable to them, especially anxiety disorders. Students experience anxiety due to several factors, including academic demands, economic conditions, and a lack of emotional support from those closest to them. The purpose of this study is to determine the condition of students when facing anxiety in the lecture process, the interventions used to reduce anxiety in students, the role of journaling in reducing anxiety, and the application of visual elements in journaling. This study uses the Systematic Literature Review (SLR) method with the PRISMA approach, through the stages of identification, screening, and inclusion. The results of the study show that students experiencing anxiety need an intervention to reduce their anxiety levels. There are several interventions found, one of which is journaling. However, journaling is considered to provide insufficient motivation for students to do it consistently. Therefore, an additional approach is needed in the form of applying visual elements in journaling to increase motivation and the relaxation effect on students with anxiety.